Schistosomiasis mansoni of the bladder simulating bladder cancer: a case report - Casella,Mário Luis (2009)
The relationship between bladder tumors and Schistosoma haematobium is well known, but only sporadic cases of bladder infection due to Schistosoma mansoni have been reported. In this case, a 48-year-old woman with macroscopic hematuria, dysuria and a palpable abdominal mass was investigated. Ultrasound showed a large exophytic mass in the bladder. Transurethral resection of the bladder revealed viable eggs of Schistosoma mansoni. The patient was treated clinically with oxamniquine and surgery was performed to resect the large mass. This case shows that schistosomiasis Mansoni in the bladder can simulate bladder cancer.